Exploring the expectations of transport professionals concerning the future automobility system: visions, challenges, and transitions - Morton, Craig; Budd, Thomas; Harrison, Gillian; Mattioli, Giulio (Taylor & Francis, 2017)
A mixture of potentially significant changes in technology, commercial structures, and social practices is currently entering the automobility system. These changes have the potential to combine together and lead to a substantial shift in the manner in which society fuels, owns, and makes use of its cars. This paper reports a research project that made use of focus groups to examine the narratives of British transport professionals concerning forthcoming developments in the automobility system. Specific attention was given to what the expectations for future change in automobility are, if these changes will likely lead to a transition toward a more sustainable system and the manner in which a transition of this nature could be facilitated. The oral testimony offered during the focus groups has been assessed qualitatively using thematic analysis. The results suggest that there is a commonly held view that the automobility system is entering a stage of flux, which may lead to considerable changes in system configuration. However, the attainment of a sustainable transition for the system will likely be inhibited by a series of institutional, societal, and physical barriers, which may restrict system developments.
Keywords: Automobility; sustainable transitions; transport futures